Coral Reef Conservation For Blue Economy and Community-Based Sustainable Tourism in Pandanan Beach, North Lombok - Bratayasa, I Wayan; Satria Prayuda, Danu; Martayadi, Uwi (Language Assistance, 2025)
This article explores a collaborative conservation initiative implemented at Pandanan Beach, Malaka Village, Pemenang Sub-district, North Lombok Regency. Coinciding with the celebration of World Oceans Day and Coral Triangle Day on June 8, 2025, the activity highlights the importance of coral reef ecosystems, seagrass beds, and tropical fish diversity as the foundation of a community-based blue economy and sustainable tourism. Engaging multiple stakeholders—including the Malaka Village Government, the Pandanan Beach Community Group led by Mr. HM. Syukur, the Coastal and Marine Resource Management Center (BPSPL) Denpasar, PLTU's CSR program, and academics—the program aimed to rehabilitate damaged coral reefs and enhance community awareness and capacity in managing coastal resources. This article analyzes the initial impact of this multi-stakeholder collaboration on conservation efforts and the potential for sustainable local economic development.